Adaptação e satisfação do expatriado por QCA: a influência comparada do trabalho significativo em expatriados confessionais e empresariais - Santos, Eduardo Lopes dos (2022)
This study focused on expatriates/family adjustment, their effects on expatriates’ job and life satisfaction, and the potential intervening role of the perception of meaningful work in such relationship between adjustment and satisfaction. The study includes a paired, comparative sample of 101 corporate and confessional expatriates, spread across 25 countries, with data collected via surveys using a longitudinal design (multiple waves in time) using scales previously validated in the literature for each construct involved. The results of the regression analyses fully or partially support most of the hypotheses predicted in the initially proposed model. The supplemental comparison using qualitative comparative analysis (QCA) between the confessional and corporate expatriate samples allowed us to propose a second model and supplemental hypotheses, concluding that the expectation, and presence of meaningful work leverages the effect of some dimensions of expatriate’s adaptation on their job and life satisfaction. The results of the study, its limitations and theoretical and practical implications are discussed and stress the importance of understanding meaningful work and its effects and antecedents for expatriates and for individuals in organizations in general, as well as the gap observed in the scientific investigation, i.e., the meaningful work being overlooked in the context of expatriates, is not justifiable.